ONLINE K–12 EDUCATION: OPPORTUNITIES FOR COLLABORATION WITH HIGHER-EDUCATION - Thompson, Melody M. (Online Learning, 2006)
It is common practice for researchers and developers of innovative programs, as well as for the foundations and agencies that provide support for such research and programming, to target their efforts on specific segments of the educational system: K–12 or higher education, for example. However, the growing acceptance of the idea that society as a whole will benefit from a move toward a seamless “K–16” system suggests that such compartmentalization is no longer appropriate, whether for traditional or online education. This paper addresses issues of how and in what ways those in K–12 and higher education can fruitfully collaborate in three growing areas of online practice: dual (or concurrent) enrollment programs for high-school students, alternative routes for teacher certification for mid-career changers, and professional development for practicing teachers.